Analysis of Junior High School Student’ Mathematics Learning difficulties on the Material of “ Relation and Function” - T Dwi Hastuti; Riyadi Riyadi; Dewi Retno Sari S (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
This research tries to analyze the mathematics learning difficulties of Junior High school students on the material of “ relation and function”. This research was conducted on the grade VIII students in one of Junior High School 1st semester in Surakarta city in the academic year 2016. Mastery of students to the concept of mathematics which is the basic science of all sciences is still lacking. The results of the national exam of junior high school students of Surakarta are still low, one of which can be seen from the absorption of material relations and functions. This is because the results of National Examination for the city of Surakarta, can be seen from the absorption of UN value in 2015 with indicators to solve problems related to the function of 57.23%, while the year 2016 with indicators determine the value of the function if the formula of the known function of 52.70 %. This study uses test methods and interviews to find out the learning difficulties and their causes. Based on the test and interview on 3 Junior high school students who have high, medium and low learning achievements, it is found that students got difficulties in determining the value of function and value of x, if the image of x is known. Students get difficulty in solving problems related to the function and determine the value of the function and determine the value of x if the image of x is given. By knowing the difficulties faced by students expected teachers can find ways to overcome difficulties faced by students so that will be able to improve students' understanding of the material relations and functions.